Smart Routing For Solid Waste Collection - Ngiam, John Tze (Universiti Malaysia Sarawak (UNIMAS), 2023)
This project aims to design and develop a route optimization and decision support system for solid waste collection in Malaysia. The problem of waste management in Malaysia has become increasingly complex due to an increase in waste generation and insufficient technology, manpower, and facilities. The current method of waste collection, used by both private and government agencies, is to conduct a real-time study of citizens' habits and movements before formulating a route plan. However, this method has proven to be inefficient and costly due to weak scheduling, inadequate road networks, a lack of advanced technologies, and poor routing. The proposed solution is to implement a route optimization algorithm to predict the probability of each feasible route for the garbage truck collection. The algorithm will take into account factors such as the capacity and power of the truck, and the workload assigned to the crew. The algorithm will be evaluated through simulations and field testing in a residential area in Kuching. The results of the evaluation will be used to design and develop a web-based application for route management, which will be made available to waste collection companies and garbage truck drivers. Based on the chosen methodology, details requirement analysis, system design, database design, and wireframe for proposed system have also been completed, and will be used to develop the system in the next phase. The implementation phase involves detailed requirement analysis, system design, database design, and wireframe creation. The system will provide waste collection companies and garbage truck drivers with a userfriendly platform for optimizing routes. Testing is conducted to validate the functionality and performance of the system. Finally, the conclusion highlights the accomplishments of the project, including the successful development of the route optimization algorithm and the web-based application. Limitations and constraints are identified, such as data availability and hardware limitations, which suggest areas for future work. Overall, this project contributes to improving waste collection operations in Malaysia, but further enhancements and advancements are needed to address the identified limitations and constraints